Regional Program for Enterprise and Innovation in Engineering: a Collaborative Experience to Promote Enterprise in Engineering Careers - Braidot, Néstor; Cesar, Ruben; González, Victoria (Ingeniería Solidaria, 2015)
This is a case report on the Regional Program for Enterprise and Innovation in Engineering (precitye from its Spanish acronym) carried out by representative institutions in the training of engineers in Argentina (confedi), Chile (condefi), Brazil (abenge) and Uruguay (anii). The article addresses relevant aspects of this program, which had support from entities responsible for higher education in the above-mentioned countries and from the “Regional Public Goods Program” of the Inter-American Development Bank. Starting with an analysis of the context and linking it to the policies of the confedi (Federal Council of Deans of Engineering of the Republic of Argentina), a description was made of the situations that facilitated the unprecedented development, because of both its scope and distributed logic, along with participation by professors from four countries in determining the critical parameters of the different activities and products. Details are given about the fundamental theories in the field of education for entrepreneurship or entrepreneurial education, which served as a guide in designing the program and defining its activities. A final section briefly describes the products generated, which then led to the creation of goods for public consumption. The article concludes with the need to address the complex processes of continuous improvement of engineering teaching through collaborative schemes among representative institutions that group together academic training units for engineers.
Keywords: institutional cooperation and coordination; venture creation; entrepreneurial education; training of engineers